Fingerprints of the visible hand: Chandlerian organizations and their inward looking malaise - Alfonso Gambardella; Marco S. Giarratana (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
This paper investigates the relationships between firm organization attributes, namely a structure á la Chandler, and their inward looking or exploitation attitude in R&D and innovation. We argue that because of sunk costs and learning processes an inward looking behavior is a consequence of increases in firm size. However, it is also produced by an organizational model based on hierarchical managerial decisions, typical of the Chandlerian firms, that is not directly related to size. We find that the US States populated by larger firms show a higher share of patent self-citations normalized by their share of world patents. Even after controlling for firm size, a proxy for the extent of firm divisionalization in the States exhibits a significant effect on patent self-citations normalized by patent shares. This supports our point that the inward looking behavior of the Chandlerian firms is not just a consequence of size, but also of the Chandlerian organizational model. Among other things, this suggests that exploration, which leads to the opening of new innovation trajectories, requires not only small firms, but also different organizational setups and decision processes.
Keywords: O32; D21; 330; Patents; Self-citations; Chandlerian Firm; Inward looking; Inertia; Patent; Unternehmensorganisation; Betriebsgröße; Forschung; Innovation; Theorie